A Literary Analysis and Authentication of Honor and Dignity (al-‘Izzah wa al-Karamah) in Sīrah Perspective - Shahzadi Pakeeza; Junaid Akbar (Journal of Islamic and Religious Studies, 2019)
Islam endows men and women with “Human Honour and Dignity” (al-‘Izzah wa al-Karamah) and provides them with directions and guidelines to protect each other’s rights with respect and honour. This research paper demonstrates the protection of honor and dignity as a significant tool of life. The denotation of “honor” and “dignity” according to the Qur’ānic and prophetic perspective has been focused in this research. In the preservation of human personal honor, dignity and other rights, Shari’ah evidences from Qur’ān and Sīrah are explored with the perspective of highlighting the emphasis on Shari’ah on this aspect of religion, which is also one of the dimensions of Maqaṣid al-Shari‘ah as well. The paper ends with the note that human beings should endure the "best moral and ethical values" of mercy, faith, compassion, justice, piety, empathy and also with the fear of abusing one’s honor and status in the society.